Synthesis, Analytical and Spectral Studies of Novel Schiff Base Complexes of Th(IV) and UO2(VI) Along with their X-Ray Diffraction Data and Toxic Effects - Sonal Agnihotri; Kishor Arora (E-Journal of Chemistry)
Schiff base was obtained using furfuraldehyde and 2-amino pyridine to prepare new complexes of thorium(IV) and dioxouranium(VI) metals by various anions. The synthesized ligands and complexes were analytically studied through spectral data, elemental analysis and conductance measurements along with x-ray diffraction pattern. The complexes showed various coordination number and their toxic effects to bacterial and fungal genus was studied by two different methods of measurement.